2013
DOI: 10.1073/pnas.1217750110
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment is associated with distinct genomic and epigenetic profiles in posttraumatic stress disorder

Abstract: Childhood maltreatment is likely to influence fundamental biological processes and engrave long-lasting epigenetic marks, leading to adverse health outcomes in adulthood. We aimed to elucidate the impact of different early environment on disease-related genomewide gene expression and DNA methylation in peripheral blood cells in patients with posttraumatic stress disorder (PTSD). Compared with the same trauma-exposed controls (n = 108), geneexpression profiles of PTSD patients with similar clinical symptoms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
348
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 479 publications
(369 citation statements)
references
References 49 publications
9
348
0
4
Order By: Relevance
“…Methylation can change the threedimensional formation of the chromatin (Li & Reinberg, 2011), and subsequently affect gene transcription. DNA methylation is thought to be influenced by prenatal (BouwlandBoth et al, 2015;Cao-Lei et al, 2014;Mychasiuk, Ilnytskyy, Kovalchuk, Kolb, & Gibb, 2011;Rijlaarsdam et al, 2017) and postnatal life events (Hughes et al, 2009;Mehta et al, 2013;Murgatroyd et al, 2009), as well as by genetic background. It can therefore be seen as the dynamic interface between genes and the environment (Meaney, 2010;Van IJzendoorn, Bakermans-Kranenburg, & Ebstein, 2011).…”
mentioning
confidence: 99%
“…Methylation can change the threedimensional formation of the chromatin (Li & Reinberg, 2011), and subsequently affect gene transcription. DNA methylation is thought to be influenced by prenatal (BouwlandBoth et al, 2015;Cao-Lei et al, 2014;Mychasiuk, Ilnytskyy, Kovalchuk, Kolb, & Gibb, 2011;Rijlaarsdam et al, 2017) and postnatal life events (Hughes et al, 2009;Mehta et al, 2013;Murgatroyd et al, 2009), as well as by genetic background. It can therefore be seen as the dynamic interface between genes and the environment (Meaney, 2010;Van IJzendoorn, Bakermans-Kranenburg, & Ebstein, 2011).…”
mentioning
confidence: 99%
“…B. Mehta et al 2013;Suderman et al 2014 (Zannas et al 2016). Genomweite Studien legen zudem nahe, dass Traumatisierungen in der Kindheit Spuren in der DNA zahlreicher Gene hinterlassen.…”
Section: Epigenomweite Studienunclassified
“…Research is increasingly identifying the links between child maltreatment and epigenetic mechanisms such as increased DNA methylation and subsequent health consequences. A recent study demonstrated that different epigenetic profiles emerged within a trauma-exposed sample with posttraumatic stress disorder (PTSD) (38), and the findings indicated that DNA methylation changes were much higher among those who had been exposed to childhood trauma. Future research should explore the influence of epigenetic mechanisms on different abuse typologies.…”
Section: Future Researchmentioning
confidence: 99%